Democratic education in technology-mediated postgraduate nursing: Equity and access in resource-limited contexts - Bokang Amelia Mahlelehlele; Jeanette Elizabeth Maritz; Gisela Hildegard van Rensburg (Interdisciplinary Journal of Sociality Studies, 2025)
This study explores how Master of Nursing Science students navigate technology-mediated learning and institutional support, examining how digital platforms either promote or hinder equitable access in resource-limited contexts through a critical pedagogy lens. A qualitative research approach, specifically constructivist grounded theory, was used to explore the problem. Data were collected during three focus group discussions involving 24 Master of Nursing Science students from the National University of Lesotho. The analysis identified key structural barriers, including unreliable internet connectivity, inadequate training on digital platforms, and disparities in technological literacy, which constrained students’ full participation in online learning. In response to these challenges, students developed adaptive strategies such as peer support networks, self-directed learning, and emotional resilience. However, relying on individual agency rather than systemic transformation underscores the persistent inequities that postgraduate students experience in resource-limited contexts. The findings highlight the need for universities to transition from passive resource provision to proactive institutional engagement, ensuring structured support that fosters meaningful learning experiences. To achieve equitable access in technology-mediated postgraduate nursing education, institutions must invest in digital infrastructure, faculty development, and psychosocial support mechanisms. This study contributes to the discourse on democratic education by advocating for systemic reforms that promote inclusive and participatory learning environments in postgraduate nursing education.